Chemical composition, structure and properties of glass and glass-ceramic materials in the system of BaO(PbO)-B2O3-Al2O3-TiO2 - Ruiz Valdés, Juan Jacobo; Gorokhovsky, A.; Escalante García, José Iván (Universidad Autónoma de Nuevo León, 2011)
The vitrification and crystallization of glasses in the system BaO(PbO)-B2O3-Al2O3-TiO2, containing (mol%): BaO (24.6-28.1), PbO (2.8-3.2), B2O3 (7.6-24.0), Al2O3 (15.9-25.5), TiO2 (39.1-41.1) were investigated. The batch compositions of different oxide molar ratios were fused in an electric furnace in a platinum crucible at 1450ºC for 2h and cast into cylindrical-shaped samples. The obtained glasses were crystallized at 950ºC for 2h. BaTiO3 was recognized as a dominant crystalline phase in the produces glass-ceramic materials. The influence of B2O3 and Al2O3 contents on the chemical resistance, mechanical strength and dielectric properties was investigated. It is shown that the glass compositions containing (mol%): B2O3 7-25 and Al2O3 16-20 displayed the optimal combinations of exploitation properties. The influence of liquid phase separation on the abovementioned properties was also analyzed.